Mesoscale features create hotspots of carbon uptake in the Antarctic Circumpolar Current. (April 2017) - Jones, Elizabeth M.; Hoppema, Mario; Strass, Volker; Hauck, Judith; Salt, Lesley; Ossebaar, Sharyn; Klaas, Christine; van Heuven, Steven M.A.C.; Wolf-Gladrow, Dieter; Stöven, Tim; de Baar, Hein J.W.
Abstract: The influence of eddy structures on the seasonal depletion of dissolved inorganic carbon (DIC) and carbon dioxide (CO2 ) disequilibrium was investigated during a trans-Atlantic crossing of the Antarctic Circumpolar Current (ACC) in austral summer 2012. The Georgia Basin, downstream of the island of South Georgia (54-55°S, 36-38°W) is a highly dynamic region due to the mesoscale activity associated with the flow of the Subantarctic Front (SAF) and Polar Front (PF). Satellite sea-surface height and chlorophyll-a anomalies revealed a cyclonic cold core that dominated the northern Georgia Basin that was formed from a large meander of the PF. Warmer waters influenced by the SAF formed a smaller anticyclonic structure to the east of the basin. Both the cold core and warm core eddy structures were hotspots of carbon uptake relative to the rest of the ACC section during austral summer. This was most amplified in the cold core where greatest CO2 undersaturation (−78 μatm) and substantial surface ocean DIC deficit (5.1 mol m −2 ) occurred. In the presence of high wind speeds, the cold core eddy acted as a strong sink for atmospheric CO2 of 25.5 mmol m −2 day −1 . Waters of the warm core displayed characteristics of the Polar Frontal Zone (PFZ), with warmer upper ocean waters and enhanced CO2 undersaturation (−59 μatm) and depletion of DIC (4.9mol m −2 ). A proposed mechanism for the enhanced carbon uptake across both eddy structures is based on the Ekman eddy pumping theory: (i) the cold core is seeded with productive (high chlorophyll-a) waters from the Antarctic Zone and sustained biological productivity through upwelled nutrient supply that counteracts DIC inputs from deep waters; (ii) horizontal entrainment of low-DIC surface waters (biological uptake) from the PFZ downwell within the warm core and cause relative DIC-depletion in the upper water column. The observations suggest that the formation and northward propagation of cold core eddies in the region of the PF could project low-DIC waters towards the site of Antarctic Intermediate Water formation and enhance CO2 drawdown into the deep ocean.